(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
The current study is based on the Schema Therapy developed by Jeffrey Young and aims to describe a discriminative profile of individuals with a history of physical marital violence and from individuals that does not show history. The sample consisted of 341 participants. The instruments used were: Young Schema Questionnaire, Revised Conflict Tactics Scale and the Family Background Questionnaire. A discriminative function among individuals with a history of physical marital violence in the current relationship and individuals with no history violence were found (χ2 = 43.098, p = 0.045) by grouping the variables: mistrust/abuse schema, defectiveness/shame schema, dependence/incompetence schema, subjugation schema and social isolation schema towards the individuals with a history of marital violence. The individuals without a history of marital violence were characterized by greater functionality in the family of origin, characterized by the absence of father´s physical abuse, sexual abuse, maternal physical abuse, physical neglect , well as a style of adequate maternal decision, parental alliance, paternal and maternal psychological adjustment.